Perencanaan Strategis Camat untuk Meningkatkan Kualitas Pelayanan Kantor Kecamatan Cibeber Cianjur Publik - Rachmat Rachmat; Neli Yuliawati; Rani Herawati (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to analyze the influence of strategic planning and sub-district leadership on the quality of public services at the Cibeber Sub-district Office, Cianjur Regency. A quantitative approach with an explanatory research design was employed. The unit of analysis is the community as service users, with samples selected using purposive sampling. Data were analyzed using SEM-PLS to examine the relationships among variables.The results indicate that the sub-district head’s strategic planning has a positive and significant effect on public service quality, with an effect size of 0.557. Leadership also shows a positive and significant effect, with a contribution of 0.414. Collectively, both variables explain a substantial portion of the variation in public service quality, highlighting the critical role of managerial and leadership factors in improving services. These findings confirm that public service quality can be enhanced through well-structured planning and effective leadership in managing public officials. Therefore, strengthening strategic planning capacity and leadership at the sub-district level is essential to achieving more optimal, responsive, and citizen-oriented public services.